Doxorubicin-conjugated siRNA lipid nanoparticles for combination cancer therapy - Butowska, Kamila; Han, Xuexiang; Gong, Ningqiang; El-Mayta, Rakan; Haley, Rebecca M.; Xue, Lulu; Zhong, Wenqun; Guo, Wei; Wang, Karin; Mitchell, Michael J. (Acta pharmaceutica Sinica. B, 2023)
Evasion of apoptosis is a hallmark of cancer, attributed in part to overexpression of the anti-apoptotic protein B-cell lymphoma 2 (Bcl-2). In a variety of cancer types, including lymphoma, Bcl-2 is overexpressed. Therapeutic targeting of Bcl-2 has demonstrated efficacy in the clinic and is the subject of extensive clinical testing in combination with chemotherapy. Therefore, the development of co-delivery systems for Bcl-2 targeting agents, such as small interfering RNA (siRNA), and chemotherapeutics, such as doxorubicin (DOX), holds promise for enabling combination cancer therapies. Lipid nanoparticles (LNPs) are a clinically advanced nucleic acid delivery system with a compact structure suitable for siRNA encapsulation and delivery. Inspired by ongoing clinical trials of albumin-hitchhiking doxorubicin prodrugs, here we developed a DOX-siRNA co-delivery strategy via conjugation of doxorubicin to the surface of siRNA-loaded LNPs. Our optimized LNPs enabled potent knockdown of Bcl-2 and efficient delivery of DOX into the nucleus of Burkitts’ lymphoma (Raji) cells, leading to effective inhibition of tumor growth in a mouse model of lymphoma. Based on these results, our LNPs may provide a platform for the co-delivery of various nucleic acids and DOX for the development of new combination cancer therapies. LNPs have been shown to efficiently encapsulate siRNA and enable potent intracellular delivery for gene knockdown. Doxorubicin-conjugated siRNA LNPs were engineered to achieve potent chemo- and RNA interference therapy. [Display omitted]